2021
DOI: 10.4236/jss.2021.97028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Factors Affecting Contractors Tender for Project Construction: An Empirical Study of Small Scale Indigenous Contractors in Awka, Nigeria

Abstract: In Nigeria and other countries' economies, small scale indigenous contractors perform a vital role that significantly impacts economic stability. The small-scale indigenous contractors contribute prominently to the economy by creating more noteworthy work openings, making higher creation volumes, growing conveys, and introducing progression and business capacities in the construction industry. In this research study, a total sample of 250 was used out of 400 small-scale indigenous contractors and other profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…An improved algorithm for dynamically adjusting the inertia weights based on fuzzy rules is proposed. e main idea of the algorithm is to use the inertia weights to formulate fuzzy inference rules and the corresponding affiliation functions, so as to determine the increment of inertia weights [16]. e test results show that the fuzzy adaptive method has better results compared with the method with linearly decreasing inertia weights.…”
Section: Related Workmentioning
confidence: 99%
“…An improved algorithm for dynamically adjusting the inertia weights based on fuzzy rules is proposed. e main idea of the algorithm is to use the inertia weights to formulate fuzzy inference rules and the corresponding affiliation functions, so as to determine the increment of inertia weights [16]. e test results show that the fuzzy adaptive method has better results compared with the method with linearly decreasing inertia weights.…”
Section: Related Workmentioning
confidence: 99%
“…Studies have also found that project duration is considered one of the least important factors in the tender phase [29,30]. It has been emphasized that lower costs should not be the only basis for choosing contractors, as time and performance factors should also be considered [31]. These findings show that the construction duration in the tender phase has not been extensively studied, although many factors have been considered in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, a different state of affairs is observed in the public construction industry in Turkey (Yitmen and Dikbaş 2002;Birgonul et al 2007;Erbaş and Çıracı 2013;Akkaynak 2014;Usta 2014), wherein legal regulations disregard planning and prioritize only the lowest tendered price (Türesoy 1989;Karapinar 2005;Tokalakoglu 2010;Kaplan 2012). Lower costs should not be the only basis for selecting contractors; time and performance factors should also be considered (Obodo et al 2021). Moreover, better tender offer systems and effective plans focusing on development have not been implemented (DPT 2001(DPT , 2007Turkish Republic Presidency of Strategy and Budget 2019).…”
Section: Introductionmentioning
confidence: 99%